Covid-19: The Global Pandemic and its Impact on the Indonesia Economy - Rif'atul Fitriyah; Ikbar Luqyana (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
2019-nCoV is officially referred to as SARS-CoV-2 and is a major cause of a disease called Covid-19. Indonesia announced the first victims of this epidemic of 2 people on 2 March 2020 then. Until March 29, 2020, the number of victims continues to grow reaching 1,285 people. This pandemic occurs at a global level, causing the industrial world to decline and it seems that some industrial organizations cannot survive as a result of this pandemic. The objective of this study is to analyze the impact of the Covid-19 outbreak which impacted on economic shocks in Indonesia. The economic shocks represented in this study are a decrease in people's purchasing power and turnover of business actors to a decrease in tax performance as a source of state revenue. The analytical method used in this research is to use a variety of policies decided by policy makers as an effort to save Indonesia from a prolonged economic crisis. The results showed that the Indonesian economy experienced a decline, ranging from the taxation sector to the stock market. The decline was the worst compared to the crisis that occurred in 1998 and the lowest in Asia.